2005
DOI: 10.1017/s0967199405003096
|View full text |Cite
|
Sign up to set email alerts
|

Haploidy influences Bak and Bcl-xL mRNA expression and increases incidence of apoptosis in porcine embryos

Abstract: The objective of this study was to determine developmental pattern, total cell number, apoptosis and apoptosis-related gene expression in haploid and diploid embryos following parthenogenetic activation. In vitro-matured porcine oocytes were activated by electrical pulses and cultured in the absence or presence of cytochalasin B for 3 h. Zygotes with two polar bodies (haploid) and one polar body (diploid) were carefully selected and were further cultured in NCSU 23 medium containing 0.4% bovine serum albumin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
3
11
0
2
Order By: Relevance
“…Interestingly, haploidy increases the incidence of apoptosis in preimplantation embryos, while parthenogenetic activation and parthenogenesis themselves would not lead to apoptosis (Liu et al 2002a, 2002b, Jeong et al 2005. Haploidy is also responsible for diminished blastocyst rates over normal embryos and diploid parthenotes (Henery & Kaufman 1992, Jeong et al 2005. Therefore, the enhanced diploidy we found in parthenotes is consistent with their AI (that was not increased) and improved development rates.…”
Section: Development and Gene Expression In Parthenotessupporting
confidence: 62%
See 1 more Smart Citation
“…Interestingly, haploidy increases the incidence of apoptosis in preimplantation embryos, while parthenogenetic activation and parthenogenesis themselves would not lead to apoptosis (Liu et al 2002a, 2002b, Jeong et al 2005. Haploidy is also responsible for diminished blastocyst rates over normal embryos and diploid parthenotes (Henery & Kaufman 1992, Jeong et al 2005. Therefore, the enhanced diploidy we found in parthenotes is consistent with their AI (that was not increased) and improved development rates.…”
Section: Development and Gene Expression In Parthenotessupporting
confidence: 62%
“…Frequency of diploid blastocysts was reported to be lower in parthenotes than in IVF embryos (Wang et al 2008). Interestingly, haploidy increases the incidence of apoptosis in preimplantation embryos, while parthenogenetic activation and parthenogenesis themselves would not lead to apoptosis (Liu et al 2002a, 2002b, Jeong et al 2005. Haploidy is also responsible for diminished blastocyst rates over normal embryos and diploid parthenotes (Henery & Kaufman 1992, Jeong et al 2005.…”
Section: Development and Gene Expression In Parthenotesmentioning
confidence: 99%
“…Nothing is known about the role of BAK1 during early development of the preimplantation bovine embryos; however, BAK1 has been shown to be involved in the regulation of apoptosis during early embryogenesis of the pig [34,35], human [36], and mouse [37], in a developmental stage-specific manner. Although elevated expression of BAK1 has been shown to play a critical role in the induction of apoptosis by inducing permeabilization of the mitochondrial outer membrane and by forming complexes with the protective BCL2-L1 proteins [38], the experimental evidence suggests that post-transcriptional and/or post-translational modification is also involved in regulation of BAK1 activation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several studies have shown an important role of BCL2-L1 in the regulation of embryonic cell death in pig [18,34,35,41], mouse [42], human [43], and cattle [44][45][46]. In contrast, some studies have shown that the levels of BCL2-L1 transcripts did not correlated with blastocyst quality [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Esta família está subdivididas em dois grupos: Proteínas pró-apoptóticas (Bax, Bad, Bid, Bcl-xS, Bak, Box, Bik, Blk, Bim, HrK, BNIP3), localizadas principalmente na membrana externa da mitocôndria e proteína anti-apoptóticas (Bcl-2, Bcl-xl, Bcl-w, A1, Mcl-1), localizadas no envelope nuclear e no retículo endoplasmático (SPANOS et al, 2002;JEONG et al, 2005). O balanço de proteínas pró e anti-apoptóticas é o que determina se a célula entrará ou não em apoptose (BETTS; KING, 2001;SPANOS et al, 2002).…”
Section: Bcl-2unclassified